Xanthine oxidase inhibitors isolated from Piper nudibaccatum. (June 2015) - Liu, Hong-Xin; He, Meng-Ting; Tan, Hai-Bo; Gu, Wei; Yang, Shi-Xian; Wang, Yue-Hu; Li, Ling; Long, Chun-Lin
Graphical abstract: Highlights: Two new hydroxychavicol derivatives were isolated from Piper nudibaccatum . Hydroxychavicol and 5 analogs (1 –5 ) were evaluated for their XO inhibitory activity. Neotaiwanensols B (3 ) showed a greater xanthine oxidase (XO) inhibitory effect. Abstract: Two new hydroxychavicol analogs nudibaccatumin A (1 ) and B (2 ), together with twenty known compounds were isolated from the methanol extract of Piper nudibaccatum . Their structures were elucidated by extensive spectroscopic analyses (1D and 2D NMR, HRESIMS, UV, IR and polarimetry). Hydroxychavicol is a known inhibitor of xanthine oxidase (XO). In the present study, hydroxychavicol and 5 natural analogs (1 –5 ) were evaluated for their XO inhibitory activity. Neotaiwanensol B (3 ) (IC50  = 0.28 μM) showed a greater inhibitory effect than hydroxychavicol and allopurinol (the positive control). Two new compounds 1 and 2 showed a moderate inhibition activity with an IC50 value of 62.94 μM and 70.67 μM, respectively.